Inequality in Person Data Protection for Vulnerable Communitiesin the Digital - Nur Arifin, Firman; Prastyanti, Rina Arum (West Science Law and Human Rights, 2025)
This study aims to analyze the inequality of personal data protection for vulnerable groups in Indonesia in the context of digital transformation. The scope includes communities with low digital literacy, remote areas, the elderly, and informal sector workers. The methods used are literature study, policy analysis, survey analysis, and case studies. Data were taken from 94 cases of personal data leaks from 2019–2023, with the majority coming from private electronic system organizers. The findings show that data protection tends to be a luxury item that is only enjoyed by empowered groups. According to the data, there were 35 cases of leaks in 2023 alone. This study also proposes a social justice-based governance model to address structural inequality for vulnerable groups.